Experimental and Finite Element Analysis Evaluation of the Effect of Variable Parameters on Tensıle Capacity in Knife Plate Connections - AYDIN, ELİF; Alemdar, Fatih (Springer Science and Business Media Deutschland GmbH, 2025)
Welded knife plate connections are widely used in steel bridge construction and play a critical role in structural elements subjected to variable and repeated loading, particularly due to traffic-induced dynamic effects. These connections are vulnerable to fatigue-related damage over time, potentially compromising structural integrity. Therefore, understanding the influence of key parameters on the tensile capacity of such connections is essential for ensuring safe design, extending service life and achieving cost-effective structural solutions.This study systematically investigates the effects of weld length, the gap between the knife plate and the hollow structural section (HSS) and various profile geometries on the tensile performance of knife plate welded connections. Unlike most previous studies that focus on a single parameter, this research adopts a comprehensive parametric approach and contributes to a deeper understanding of the interactions between multiple design variables. The methodology integrates experimental testing with numerical simulations conducted using the ABAQUS finite element software. A total of 15 full-scale tensile experimental tests were carried out and the results were compared with numerical predictions. The findings indicate a strong correlation between the experimental and numerical results with the finite element model achieving over 90% accuracy. These results validate the reliability of the numerical approach and demonstrate its potential to reduce dependence on experimental testing in future optimization and design studies offering significant savings in both time and cost.
Keywords: FEM; Knife-plate Connection; Slot Gap; Tensile Strength; Weld Length